Resistance to Love in Medieval English Romance : Negotiating Consent, Gender, and Desire. - Piercy, Hannah. (Studies in Medieval Romance Series, 2023)
This book explores resistance as a widespread motif in medieval romance to consider themes of consent, gender, and desire in medieval England.